Increased serum anti-ceramide antibodies and decreased sphingosine-1-phosphate levels in patients with obstructive sleep apnea syndrome as potential markers of endothelial dysfunction - Wiśniewski, Andrzej; Wiśniewska, Elżbieta; Lewandowski, Łukasz; Nowak, Izabela; Kosacka, Monika (Frontiers in Molecular Biosciences, 2025)
ObjectiveSphingosine-1-phosphate (S1P) and ceramide are bioactive sphingolipids that have been associated with some obstructive sleep apnea (OSA) comorbidities like coronary artery disease (CAD), insulin resistance, diabetes mellitus, hypertension, cardiac dysfunction, and ischemic stroke. On the other hand, S1P and ceramide play key roles in maintaining endothelial homeostasis, which is impaired by repetitive hypoxia/reoxygenation and sleep fragmentation characteristic of OSA. Since the exact role of S1P and ceramide in OSA is still poorly explored, the present study aimed to compare the levels of S1P and anti-ceramide antibodies (ceramide-Ab) in OSA patients and controls.MethodsWe recruited 153 subjects (104 patients and 49 controls). The concentrations of anti-ceramide antibodies and S1P were measured using the ELISA technique.ResultsWe detected significantly higher levels of anti-ceramide antibodies in the OSA group than in the control group (median 318.0 vs. 247.7 ng/mL, p < 0.0001). By contrast, S1P levels were markedly higher in the controls than in the OSA patients (median 1,006.0 vs. 573.9 ng/mL, p < 0.0001). No correlation was observed between either ceramide-Ab or S1P concentrations and the following variables: OSA severity (AHI), desaturation index (DI), BMI, average SaO2, minimum SaO2, and C-reactive protein (CRP). Additionally, we noted a positive correlation between BMI and AHI (Spearman r = 0.5051, p < 0.0001), as well as between BMI and DI (Spearman r = 0.55, p < 0.0001). Conversely, BMI negatively correlated with mean SaO2 (Spearman r = - 0.58, p < 0.0001) and with minimum SaO2 (Spearman r = - 0.44, p < 0.0001). A middle-strong positive correlation was observed between BMI and serum level of CRP (Spearman r = 0.60, p < 0.0001).ConclusionWe demonstrated that anti-ceramide antibody levels were significantly increased, whereas S1P levels were decreased in patients with obstructive sleep apnea in comparison to healthy subjects. These results suggest that the balance between ceramide and S1P (known as sphingolipid rheostat) may be dysregulated in the course of OSA. We suggest that ceramide-Ab might become a valuable positive biomarker of the disease with S1P as a negative biomarker.